The Gulen Phenomenon: A Neo-Sufi Challenge to Turkey's Rival Elite? - Gulay, E (2007)
Fethullah Gülen's modern religious movement has been the subject of numerous academic articles and books and has received a great deal of media attention both in the West and in its native Turkey. This work builds on those findings, further analyzing the theological writings of Gülen and his followers in order to reach an understanding of their conceptions of subjectivity, worldly activity, salvation, and the role of Islam in public life. Using a constructivist paradigm that views the community in a process of mutual engagement with social-structural forces at large, its role and influence in Turkish civil society and the larger world of Islamic social movements is distilled. From this basis, a typology of Islamic social movements is constructed, and an attempt is made to locate the Gülen community within it. By doing so, this work both identifies and defines the broad features of this dynamic and growing community within its social, political, and religious context.